Study on Carbide Tool Performance in Green Machining of Aeronautical Material: Q-T Models and Finite Element Analysis - Ginting, Armansyah (IPTEK, LPPM, Institut Teknologi Sepuluh Nopember, 2008)
Through the experimental work on dry end milling of an aeronautical material Ti-6242S, the extended Taylor models for volume of material removal (Q.Vc 2.2- .fz 1.98.aa 1.96=3.318x103) and tool life (T.Vc 3.3.fz 2.97.aa 2.80- =1.531x106) are resulted for characterizing the performance of the off-centre ball end milling alloyed carbide tool (W-(Ti/Ta/Nb)C-Co). Further analysis on the models result the optimum cutting conditions (Vc 88 m/min at fz 0.20 mm/tooth, Vc 113.5 m/min at fz 0.15 mm/tooth, and Vc 163 m/min at fz 0.10 mm/tooth) as the best compromise among cutting speed (Vc), material removal rate (MRR=Q/T) (cm3 /min) and T (min). Moreover, it can be interpreted that the tool failure mode, tool wear mechanism and the behaviour of tool performance are changing at the optimum cutting conditions given by the models that plot in a chart of MRR-T-Vc. By utilizing the FEM simulation, the chip morphology, contact length at the tool-chip interface and the tribological aspects (temperature, pressure) in machining at the optimum cutting conditions can be evaluated. The results of simulation support the interpretation of experimental results.